ANALISIS REALISASI ANGGARAN UNTUK MENILAI EFEKTIVITAS DAN EFISIENSI KINERJA INSTANSI PEMERINTAH DAERAH KOTA MATARAM - Fathurrahman; Baiq Dewi Lita Andiana; Triana Lidona Aprilani; Farah Zihatul F; Hidayat, Ahmad Ridho (Fakultas Ekonomi dan Bisnis Universitas Islam Al-Azhar Mataram, 2023)
This study aims to analyze how the realization of the budget in assessing the effectiveness and efficiency of performance at the three Mataram City Regional Government Agencies. Where effectiveness is a measure of the success or failure of an organization in achieving its goals while efficiency is a measurement of achieving maximum output with the lowest possible use of resources and funds. The type of research used in this research is descriptive quantitative. The population in this study was all SKPD in Mataram City. Meanwhile, the samples used were three Mataram City Regional Government Agencies, namely: 1) Regional Development Planning Agency, 2) Youth and Sports Service, and 3) Social Service. The data used in this study is secondary data in the form of audited company annual financial reports. These data were obtained from the official website of the Mataram City Government, such as LRA from 2020- 2022 in each agency. The research results for the level of effectiveness in 2020-2022 are all in the effective category because the results of achieving an effectiveness level of more than 80 percent, can be said to be good and meet predetermined criteria. The research results for the efficiency level in 2020-2022 are all in the efficient category, said to be efficient because the efficiency level is 60-80 percent.